Respostas

A melhor resposta!
2014-07-22T18:27:29-03:00


1 + 3.√(x² - x) = x 
3.√(x² - x) = x - 1 
( 3.√(x² - x) )² = (x - 1)² 
9.(x² - x) = x² - 2.x + 1 
9.x² - 9.x = x² - 2.x + 1 
9.x² - 9.x - x² + 2.x - 1 = 0 
8.x² - 7.x - 1 = 0 

Condição: 
Para todo x real, 
√(x² - x) ≥ 0 → x² - x ≥ 0 → x.(x-1) ≥ 0 → x ≥ 0 e x ≥ 1 

∆ = (-7)² - 4.(-1).(8) 
∆ = 49 + 32 = 81 

-(-7) ± √81 / 2.(8) 
7 ± 9 / 16 

x' = 1 (OK!) 
x'' = -1/8 (Não serve) 
S = {1} 

d. 
³√(5x² +7) = 3 
( ³√(5x² +7) )³ = (3)³ 
5x² +7 = 27 
5x² = 27 - 7 
x² = 20 / 5 
x = √4 
x = ±2 

S = {-2, 2}
3 4 3